2021
DOI: 10.3889/oamjms.2021.5707
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5′nucleotidase (CD73) May Predict Occurrence and Grade of GVHD in Patients Undergoing Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: BACKGROUND: Graft versus host disease (GVHD) represents a main cause of post-transplant morbidity and mortality. Ectonucleotidases are one of major components of purinergic signaling which is one of the important mediator pathways regulating cellular functions. CD73 is the most significant member of ectonucleotidases. AIM: The aim of the study was to assess role of CD73 in development/severity of GVHD among patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) SUBJECT AND METHODS: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Inflammatory disorders in the airway are mediated in part by both enhanced levels of adenosine in the bronchoalveolar lavage fluid and by enhanced hyperresponsiveness to adenosine challenge 130 . A prospective clinical study in GVHD found that levels of the CD73 ectonucleotidase in pre‐transplant patients were inversely correlated with occurrence and grade of chronic GVHD, demonstrating an essential and prognostically useful role for CD73 in dampening the immune response in transplants 108 . Other groups who interrogated the role of purines in GVHD found that transplant regimens commonly induced the release of danger‐associated molecular patterns (DAMPs) such as ATP, and that ATP can bind to purinergic receptors on T‐cells to promote a pro‐inflammatory microenvironment that exacerbates GVHD; however, the concentration of ATP and the activation of different purinergic receptors will dictate outcomes 109 .…”
Section: Purinergic Signaling and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory disorders in the airway are mediated in part by both enhanced levels of adenosine in the bronchoalveolar lavage fluid and by enhanced hyperresponsiveness to adenosine challenge 130 . A prospective clinical study in GVHD found that levels of the CD73 ectonucleotidase in pre‐transplant patients were inversely correlated with occurrence and grade of chronic GVHD, demonstrating an essential and prognostically useful role for CD73 in dampening the immune response in transplants 108 . Other groups who interrogated the role of purines in GVHD found that transplant regimens commonly induced the release of danger‐associated molecular patterns (DAMPs) such as ATP, and that ATP can bind to purinergic receptors on T‐cells to promote a pro‐inflammatory microenvironment that exacerbates GVHD; however, the concentration of ATP and the activation of different purinergic receptors will dictate outcomes 109 .…”
Section: Purinergic Signaling and Immunitymentioning
confidence: 99%
“…Defects in purine signaling and metabolism have been wellcharacterized in several inflammatory diseases including lung disorders such as asthma [98][99][100][101][102] or chronic obstructive pulmonary disease (COPD), [103][104][105][106][107] graft-versus-host-disease (GVHD), [108][109][110][111] ischemiareperfusion injury, [112][113][114][115][116] gastrointestinal (GI) inflammation or inflammatory bowel disorder (IBD) [117][118][119][120][121][122] multiple sclerosis (MS), [123][124][125][126][127] and myasthenia gravis, 128,129 among others. Inflammatory disorders in the airway are mediated in part by both enhanced levels of adenosine in the bronchoalveolar lavage fluid and by enhanced hyperresponsiveness to adenosine challenge.…”
Section: When Purinergic Signaling Goes Awrymentioning
confidence: 99%